FEATURES OF LEGAL REGULATION OF THE PROTECTION OF ANIMAL WORLD UNDER THE LEGISLATION OF THE REPUBLIC OF UZBEKISTAN - Ibragimova Z.M (Galaxy International Interdisciplinary Research Journal, 2022)
Humane treatment of animals and their treatment is an integral and very important part of the culture of a civilized society. Cruelty to animals tends to affect people’s attitudes, and develops a cynical attitude toward moral standards. In the Address of the President of the Republic of Uzbekistan Mirziyoyev Sh.Sh. The Oliy Majlis is determined that in the desire to acquire modern knowledge, to be enlightened and to have a high culture, it should become a vital need for all of us.